ANALISIS ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) DI NEGARA ASEAN-5: STUDI KOMPARATIF PADA PERUSAHAAN TERDAFTAR TAHUN 2015-2023 - Ariska, Temi; Verawati, Dian Marlina; Yudhanto, Wildan (JURNAL MANAJEMEN, 2025)
This research aims to provide empirical evidence on trends in the application of environmental, social and governance (ESG) in ASEAN-5 countries as well as differences in the application of environmental, social and governance (ESG) among ASEAN-5 countries, namely Indonesia, Malaysia, the Philippines, Singapore and Thailand, with a focus on companies listed on the stock exchanges of each of the ASEAN-5 countries. This research uses descriptive and comparative research formswith a quantitative approach based on secondary data from Bloomberg ESG scores. This research uses a population of 5 out of 11 ASEAN countries, namely Indonesia, Malaysia, Philippines, Singapore and Thailand. The total research sample for the period 2015-2023 (9 years) was 1,683. The research results show that 1. The implementation of environmental, social and governance (ESG) in ASEAN-5 countries shows an increasing trend during 2015-2023, reflecting the increasing attention to sustainability, and 2. The research results show that there are significant differences in the implementation of environmental, social and governance (ESG) in ASEAN-5 countries with Thailand consistently ranking highest, followed by Malaysia, Singapore, the Philippines, and Indonesia at the lowest position.